Subjetivação e linguagem: um estudo sobre particularidades na apropriação de linguagem de crianças surdas; filhos (as) de pais ouvintes - CRUZ, Juacély Raquel da Conceição (2025)
The present work aims to to analyze the particularities of the language appropriation process in the subjectivation of deaf children of hearing parents. We highlight in this article the importance of parental bonds for the development of language skills that circulate spontaneously in the family environment. As theoretical support, we chose to open a dialogue with a group of authors who develop studies in the interface with psycholinguistics, among which we highlight the considerations of Solé (2005) which alerts us to the possibility of a certain negligence and ignorance on the part of hearing parents of deaf children who end up making hasty decisions regarding the linguistic development of their children. Another prominent author is Spitz (1998) which reinforces the idea of early stimulation that makes use of greater brain plasticity, which we understand as favorable to the child's global development. We consider that the decisions made by the parents in the face of the diagnosis of deafness, directly interfere in the process of subjectivation and language development and in its insertion in the school environment.